Al-Khawarij dan Al-Murjiah: Sejarah dan Pokok-Pokok Ajarannya - Almahdali, Sayyid Syahdan; Jafar, Usman; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study delves into the definitions and historical emergence of two early Islamic sects, al-Khawarij and al-Murjiah, and contrasts their core teachings. Al-Khawarij, derived from the term